Addressing the source contribution of PM2.5 on mortality: an evaluation study of its impacts on excess mortality in China. (18th October 2017) - Tian, Lin; Zeng, Qiang; Dong, Wentan; Guo, Qun; Wu, Ziting; Pan, Xiaochuan; Li, Guoxing; Liu, Yang
Abstract: We estimated PM2.5 concentrations using satellite data and population mortality values for cause-specific diseases and employed the integrated exposure–response model to obtain the associations between exposure and response. PM2.5 source apportionment data were then used to evaluate the excess mortality attributable to PM2.5 from different emission sources. In 2013, 1.07 million excess deaths were attributed to PM2.5 exposure in China. The potentially avoidable excess deaths would be 279 000, 459 000, 731 000 and 898 000 if the PM2.5 concentrations were reduced to meet WHO interim target (IT)-1 (35 μg m −3, also the Chinese standard), IT-2 (25 μg m −3 ), IT-3 (15 μg m −3 ) and the air quality guidelines (10 μg m −3 ), respectively, compared with concentrations experienced in 2013. There were 249 000 (95% CI: 115–337), 228 000 (95% CI: 105–309), 203 000 (95% CI: 94–274), 197 000 (95% CI: 91–266), and 193 000 (95% CI: 88–262) excess deaths attributed to PM2.5 from coal burning, vehicle emissions, industry-related emissions, dust and other sources in 2013, respectively. Coal burning was the main source of atmospheric PM2.5 ; it contributed the most to excess mortalities and the health effects were likely to have been conservatively estimated. Considerable health benefits could be achieved if more stringent ambient PM2.5 standards were achieved in China.